Kajian Teknis Daya Dukung Tanah untuk Menentukan Kapasitas Optimum Stockpile Utama PT Putra Muba Coal - Zella Navtalia; Hisni Rahmi; Muhammad Faisal Seprizal; Diah Wully Agustine; Dimas Agung Permadi; Andy Yanottama (Pusat riset dan Inovasi Nasional, 2025)
Settlement of the ground floor of stockpile is caused by ground pressure of coal pile which is bigger than stockpile floor bearing capacity leads to bury under of some coal. So it is needed to do a study of optimum capacity by stockpile floor bearing capacity. Study of stockpile optimum capacity is started by calculating Californian Bearing Ratio (CBR) of stockpile subgrade using dynamic cone penetrometer in some location on each of the stockpile compartment. CBR value of stockpile subgrade converted into bearing ratio, so the maximum tonage of stockpile can be known. By considerating of pile height, angle of repose of low grade coal, monthly production target, and the road geometry for mechanical equipment access purpose, the optimum capacity of PT Putra Muba Coal stockpile is 198.549,95 ton, which divided into seven coal piles.